Decision regret after reirradiation of the primary site in patients with prostate cancer - Alexander Fabian; Bilgesu Sahin Öztürk; Lars Haack; Severin Rodler; Christof van der Horst; Christian Schulz; Claudia Schmalz; Stefan Huttenlocher; Olaf Wittenstein; Oliver Blanck; Frank-André Siebert; David Krug (Clinical and Translational Radiation Oncology)
Purpose: A subset of prostate cancer patients develops local relapse at the primary site after radiotherapy. The optimal local salvage strategy is unknown. Therefore, we aimed to explore prevalence and determinants of decision regret among patients after reirradiation of the primary site. Materials and methods: We surveyed 31 patients in a cross-sectional bi-centre exploratory study. Reirradiation was high dose-rate brachytherapy (HDR-BT) in 21 and stereotactic body radiotherapy (SBRT) in 10 patients. Decision regret (DR) was measured using the Decision Regret Scale (DRS) (range: 0–100; higher values higher regret). Further patient-reported outcomes (PRO) included the EPIC-26, EORTC QLQ-C30, PRO-CTCAE, and PSCC questionnaires. Univariable associations of decision regret and potential determinants were assessed by one-way ANOVA or Pearson’s correlation. Results: Median age at reirradiation was 75 years. Median time intervals from initial radiotherapy to reirradiation was 8 years and 4 years from reirradiation to survey. The mean DRS score was 10 (SD: 14). No (0 points), mild (1–25 points), or strong regret (>25 points) was reported by 45 % (14/31), 48 % (15/31), and 7 % (2/31) of the patients, respectively. DR was significantly associated with PRO of urinary symptom burden and toxicity as well as levels of shared-decision making and patient satisfaction. HDR-BT vs. SBRT, further local relapse, and progression-free survival were not associated with DR. Conclusions: DR was mild among prostate cancer patients after reirradiation to the primary site. PRO on symptom burden and shared decision making may be associated with DR. These findings should be validated and may inform treatment decisions on local salvage therapy.